A model of American foreign trade policy - Bjelić Predrag M. (Međunarodni Problemi)
In this paper the author explains very complex and developed process of trade policy creation in the United States. He describes the institutional model of trade policy creation, main organs and procedures, and the legal setting for that process. He also gives the basic principles in the realization of American trade policy in all dimensions - bilaterally regionally and multilaterally, that is to say the bilateral relations with main American trading partners, the links of the United States with the main regional economic groupings in the world and the U. S. influence in international economic organizations.